Comparison of two tests to determine the maximal aerobic speed - Saddek, B.; Coquart, J. B. J.; Mourot, L.; Adel, B.; Moulay, I.; Bengoua, A.; Mokrani, D. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2020)
The aims of this study were (a): to compare maximal physiological responses (maximal heart rate: HRmax and blood lactate concentration: [La-]) and maximal aerobic speed (MAS) achieved during a gold standard test (T-VAM) to those during a new test entitled: the 150-50 Intermittent Test (150-50IT), and (b): to test the reliability of the 150-50IT. Eighteen middle-distance runners performed, in a random order, the T-VAM and the 150-50IT. Moreover, the runners performed a second 150-50IT (retest). The results of this study showed that the MAS obtained during 150-50IT were significantly higher than the MAS during the T-VAM (19.1 ± 0.9 vs. 17.9 ± 0.9 km.h-1, p < 0.001). There was also significant higher values in HRmax (193 ± 4 vs. 191 ± 2 bpm, p = 0.011), [La-] (11.4 ± 0.4 vs. 11.0 ± 0.5 mmol.L-1, p = 0.039) during the 150-50IT. Nevertheless, significant correlations were noted for MAS (r = 0.71, p = 0.001) and HRmax (r = 0.63, p = 0.007). MAS obtained during the first 150-50IT and the retest were not significantly different (p = 0.76) and were significantly correlated (r = 0.94, p < 0.001, intraclass correlation coefficient = 0.93 and coefficient of variation = 6.8 %). In conclusion, the 150-50IT is highly reproducible, but the maximal physiological responses derived from both tests cannot be interchangeable in the design of training programs.